An International Survey of Quality and Safety Programs in Radiology. Issue 1 (February 2021) - Dick, Jeremy; Darras, Kathryn E.; Lexa, Frank J.; Denton, Erika; Ehara, Shigeru; Galloway, Howard; Jankharia, Bhavin; Kassing, Pam; Kumamaru, Kanako Kunishima; Mildenberger, Peter; Morozov, Sergey; Pyatigorskaya, Nadya; et al.
Purpose: The aim of this study was to determine the status of radiology quality improvement programs in a variety of selected nations worldwide. Methods: A survey was developed by select members of the International Economics Committee of the American College of Radiology on quality programs and was distributed to committee members. Members responded on behalf of their country. The 51-question survey asked about 12 different quality initiatives which were grouped into 4 themes: departments, users, equipment, and outcomes. Respondents reported whether a designated type of quality initiative was used in their country and answered subsequent questions further characterizing it. Results: The response rate was 100% and represented Australia, Canada, China, England, France, Germany, India, Israel, Japan, the Netherlands, Russia, and the United States. The most frequently reported quality initiatives were imaging appropriateness (91.7%) and disease registries (91.7%), followed by key performance indicators (83.3%) and morbidity and mortality rounds (83.3%). Peer review, equipment accreditation, radiation dose monitoring, and structured reporting were reported by 75.0% of respondents, followed by 58.3% of respondents for quality audits and critical incident reporting. The least frequently reported initiatives included Lean/Kaizen exercises and physician performance assessments, implemented by 25.0% of respondents. Conclusion: There is considerable diversity in the quality programs used throughout the world, despite some influence by national and international organizations, from whom further guidance could increase uniformity and optimize patient care in radiology.